Web-Based Decision Support System for Managing Periapical Radiolucencies in Root-Filled Teeth: Development and Effectiveness With Undergraduates - Bottini, Dalia; Abella Sans, Francesc; González Sánchez, José Antonio; Abbott, Paul V.; Encinas, Marc; Irazusta, Sergio; Rico Romano, Cristina; Durán Sindreu, Fernando; García Font, Marc (Wiley, 2025)
Introduction: The aim of this study was to assess the agreement in the management of periapical radiolucencies associated with root-filled teeth among dental students using and without using a new web-based clinical decision support system (CDSS) application (DentalHelp). Materials and Methods: One hundred ten dental students from two universities were chosen to evaluate 10 cases of periapical radiolucencies associated with root-filled teeth. Each case included the clinical signs and symptoms, clinical photographs, periapical radiographs, and a small-volume cone beam computed tomography (CBCT) scan. Participants were asked to select one proposed management option and to assess the degree of difficulty in making this decision. Four weeks later, students entered case information into the DentalHelp web app. The app¿s algorithm then autonomously generated a suggested management option for each case. Cohen¿s unweighted Kappa index was calculated to estimate the level of concordance between each suggested management option for each case with and without using the app. Results: There was a significant change in the management choice by students when using the CDSS compared to when they did not use it (p < 0.05). A global Kappa index of 0.21 (95% CI: 0.17¿0.25) indicated a weak general agreement. Cohen¿s Kappa index of 0.07 (95% CI: 0.02¿0.11) demonstrated poor agreement between the level of difficulty of decision-making with and without the app. Conclusions: The DentalHelp web app was effective in assisting dental students with clinical decision-making for periapical radiolucencies associated with root-filled teeth
Keywords: clinical decision support systems | DentalHelp | periapical radiolucency | root-filled teeth